Recent advances in self‐powered and flexible UVC photodetectors. Issue 5 (25th May 2022) - Nguyen, Thi My Huyen; Shin, Seong Gwan; Choi, Hyung Wook; Bark, Chung Wung
Abstract: Ultraviolet‐C (UVC) radiation is employed in various applications, including irreplaceable applications in military and civil fields, such as missile guidance, flame detection, partial discharge detection, disinfection, and wireless communication. Although most modern electronics are based on Si, UVC detection technology remains a unique exception because the short wavelength of UV radiation makes efficient detection with Si difficult. In this review, recent challenges in obtaining ideal UVC photodetectors with various materials and various forms are introduced. An ideal photodetector must satisfy the following requirements: high sensitivity, fast response speed, high on/off photocurrent ratio, good regional selectivity, outstanding reproducibility, and superior thermal and photo stabilities. UVC detection is still in its infancy compared to the detection of UVA as well as other photon spectra, and recent research has focused on different key components, including the configuration, material, and substrate, to acquire battery‐free, super‐sensitive, ultra‐stable, ultra‐small, and portable UVC photodetectors. We introduce and discuss the strategies for fabricating self‐powered UVC photodetectors on flexible substrates in terms of the structure, material, and direction of incoming radiation. We also explain the physical mechanisms of self‐powered devices with various architectures. Finally, we present a brief outlook that discusses the challenges and future strategies for deep‐UVC photodetectors. Abstract : This review introduced and discussed strategies for fabricating self‐powered UVC photodetectors in terms of the device structure, photoactive material, and flexible substrates. Based on the summary of previous works, we presented a brief outlook of challenges and future strategies for deep‐UVC photodetectors.